MODIFIKASI MEDIA SAMSAK DARI BAN BEKAS UNTUK MELATIH TEKNIK PUKULAN DOBEL CEPAT PADA BELADIRI TARUNG DERAJAT SATLAT UNDANA - Veramyta Maria Martha Flora Babang; Maria Andriani Barek Ladjar; Semuel F. Pesingkai (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
The form of research in this thesis uses a quantitative descriptive method, while the population used in this research is 22 members of the satlatundana degree combatants in Kupang. The sample of this research is 12 people. In the data collection process, the method used is the main method which includes interview, test and measurement methods. documentation,. The interview method is used to get an explanation of the differences in doing a double-fast punch without a punching bag and using a punching bag. Tests and measurements are used to determine the ability to double-hit quickly without the media and using the media. The documentation method is used to get pictures and documents.Based on the results and discussion, it can be seen that the process of double-fast punching using a modified punching bag in the martial arts degree satlat undana kupang can be carried out well because it is supported by adequate facilities and infrastructure.